Juno's Close Encounter With Ganymede—An Overview. Issue 23 (12th December 2022) - Hansen, C. J.; Bolton, S.; Sulaiman, A. H.; Duling, S.; Bagenal, F.; Brennan, M.; Connerney, J.; Clark, G.; Lunine, J.; Levin, S.; Kurth, W.; Mura, A.; et al.
Abstract: The Juno spacecraft has been in orbit around Jupiter since 2016. Two flybys of Ganymede were executed in 2021, opportunities realized by evolution of Juno's polar orbit over the intervening 5 years. The geometry of the close flyby just prior to the 34th perijove pass by Jupiter brought the spacecraft inside Ganymede's unique magnetosphere. Juno's payload, designed to study Jupiter's magnetosphere, had ample dynamic range to study Ganymede's magnetosphere. The Juno radio system was used both for gravity measurements and for study of Ganymede's ionosphere. Remote sensing of Ganymede returned new results on geology, surface composition, and thermal properties of the surface and subsurface. Plain Language Summary: The evolution of Juno's orbit around Jupiter made it possible to execute a close and a distant flyby of Ganymede in 2021. The geometry of the close pass allowed Juno to enter Ganymede's unique magnetosphere. Juno's remote sensing instruments observed a significant area of Ganymede's surface and subsurface with higher resolution than Voyager or Galileo. Key Points: Juno passed Ganymede on 7 June 2021 at an altitude of approximately 1, 000 km, the closest any spacecraft has come since the Galileo mission ended in 2003 The path of Juno's trajectory allowed the spacecraft to pierce Ganymede's unique magnetosphere and map a swath of its surface and subsurface The geometry of the flyby is described for the close pass in June and a more distant pass (approximately 50, 000 km) on 20 July 2021